# Tuesday October 22 ## Convolution Recall: - **Continuous Compact Approximation:** $C_c \injects L^1$ is dense. - **Continuity in $L^1$:** $$ f\in L^1 \implies \norm{\tau f - f} \to 0, \text{ i.e. } \lim_{y\to 0} \int \abs{f(x+y) - f(x)} ~dx = 0 .$$ - If $f\in L^1$, then for any $\varepsilon > 0$, - **Small tails:** There exists a $\delta$ such that for all $E$ such that $$ m(E) \leq \delta \implies \int_E \abs{f} < \varepsilon .$$ - There exists an $N$ such that $$ \int_{\theset{\norm{x} \geq N}} \abs{f} < \varepsilon .$$ - Note that $\abs{f(x)} < \varepsilon ~~\forall x$ such that $\norm x \geq N$ exactly when $f$ is uniformly continuous **Definition:** The *convolution* of $f,g$ measurable functions on $\RR^n$ is given by $$ f\star g (x) = \int_{\RR^n} f(x-y) g(y) ~dy $$ for every $x$ for which this integral makes sense. **Remarks:** - There are sufficient conditions on $f,g$ which guarantee that $f\star g$ exists. - If for some $x$, the function $$ y\mapsto f(x-y)g(y) $$ is measurable, then the function $$ y\mapsto f(y)g(x-y) $$ is also integrable. > Note that this is just a translation followed by a reflection, which is still integrable since this operation is in $\GL(n, \RR))$ and $f\star g = g \star f$. ## Properties of Convolutions **Theorem 1:** a. $$ f\in L^1 \text{ and } g \text{ bounded } \implies f\star g \quad \text{ is bounded *and* uniformly continuous}. $$ b. $$ f,g \in L^1 \text{ and } f,g \text{ bounded } \implies \lim_{\abs{x}\to\infty} (f\star g)(x) = 0 .$$ > Note that (b) immediately follows if it were the case that $f\star g$ were uniformly continuous and *integrable*, but we don't necessarily need integrability for this result. > Note: It is possible to pointwise multiply 2 integrable functions and get something non-integrable -- consider $f^2$ where $$ f(x) = \frac{1}{\sqrt x} \chi_{[0,1]} .$$ **Theorem 2:** $$ f,g \in L^1 \implies \norm{f\star g}_1 \leq \norm{f}_1 \norm{g}_1,$$ and equality is attained if $f, g \geq 0$. That is, $$ \int \abs{f\star g} \leq \int\abs{f} \int\abs{g} .$$ **Corollary**: If $g$ is additionally *bounded*, then $$ \lim_{\abs x \to \infty} f\star g(x) = 0 .$$ **Theorem 3:** \begin{align*} f\in L^1, \quad g \text{ differentiable}, \quad \text{ and } g, \dd{g}{x_1}, \cdots, \dd{g}{x_n} &\text{ all bounded } \implies \\ f\star g \in C^1 \text{ and }\dd{}{x_j} (f\star g) &= f\star (\dd{}{x_j} g) .\end{align*} **Corollary**: $$ f\in L^1 \text{ and } g\in C^\infty_c \implies f\star g \in C^\infty \text{ and } \lim_{\abs x \to \infty} f\star g(x) = 0 .$$ In other words, defining $C_0$ as the functions that vanish at infinity, we have $f\star g \in C_0^\infty$. > Note that we don't necessarily preserve *compact support* after this convolution. See the following picture, which looks similar for any fixed $x$ -- particularly any large $x$. ![Image](figures/2019-10-22-11:55.png)\ *Proof of Theorem 1, part (a):* \begin{align*} \abs{\int f(x-y)g(y) ~dy} &\leq \int \abs{f(x-y)} \abs{g(y)} ~dy \\ &\leq M \int \abs{f(x-y)} ~dy \\ &\leq M \norm{f}_1 .\end{align*} and \begin{align*} \abs{f\star g(x+h) - f\star g} &= \abs{ \int f(x+h-y)g(y)~dy - \int f(x-y)g(y)~dy } \\ &\leq \int \abs{f(x+h-y) - f(x-y)} \abs{g(y)}~dy \\ &\leq M \int \abs{f(z+h) - f(z)}~dz \to 0 .\end{align*} *Proof of Theorem 1, part (b):* Let $\varepsilon > 0$, then choose $N$ such that $$ \int_{\theset{\norm{y} \geq N}} \abs{f(y)} ~dy < \varepsilon \quad \text{and} \quad \int_{\theset{\norm{y} \geq N}} \abs{g(y)} ~dy .$$ Since $\abs{x} \leq \abs{x-y} + \abs{y}$ by the triangle inequality, if we take $\abs{x} \geq 2N$, then *either* - $\abs{x-y} \geq N$, or - $\abs{y} \geq N$. In the first case, let $A_x = \theset{\abs x \geq N}$ \begin{align*} \abs{f\star g} &\leq \int \abs{f(x-y)} \abs{g(y)} ~dy \\ &\leq M \int_{A_{x-y}} \abs{f(x-y)} < M\varepsilon .\end{align*} and in the second case, take \begin{align*} \abs{f\star g} &\leq \int \abs{f(x-y)} \abs{g(y)} ~dy \\ &\leq M \int_{A_{y}} \abs{g(y)} < M\varepsilon .\end{align*} *Proof of Theorem 2:* Since $f,g \in L^1$, the function $h(x, y) \definedas f(x-y)g(y)$ will be measurable on $\RR^n\cross\RR^n$ as a product of measurable functions if we can show that the function $f_{x,y} \definedas (x,y) \mapsto f(x-y)$ is measurable. To see that this is the case, define $F(x-y, y) = f(x-y)$ by taking the cylinder, then let $$ T = \left( \begin{array}{cc} 1& -1\\ 0 & 1 \end{array}\right) \implies T(x, y) = (x-y, y) ,$$ Thus $f_{x,y}(x, y) = (F \circ T)(x, y)$. We can now note that \begin{align*} \int \int \abs{f(x-y)} \abs{g(y)} ~dy ~dx &=_{FT} \int \int \abs{f(x-y)} \abs{g(y)} ~dx ~dy \\ &= \int \abs{g(y)} \left( \int \abs{f(x-y)} ~dx \right) ~dy \\ &= \norm{f}_1 \norm{g}_1 .\end{align*} This proves that the integrand is in $L^1(\RR^{2n})$, so Fubini implies that $f\star g(x)$ is in $L^1$ for almost every $x$. But then \begin{align*} \int \abs{f\star g(x)}~dx &\leq \int \int \abs{f(x-y) g(y)}~dy~dx \\ &= \norm{f}_1 \norm{g}_1 .\end{align*} $\qed$ > Note that equality is attained here if $f, g \geq 0$.